2006
DOI: 10.1093/chromsci/44.7.438
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Method for Epichlorohydrin Determination in Water Using Headspace-Solid-Phase Microextraction and Gas Chromatography

Abstract: A simple procedure for epychlorohydrin determination in water is presented. In order to optimize the epichlorohydrin extraction conditions in water using headspace (HS)-solid-phase microextraction (SPME), followed by gas chromatography, an experimental design in two steps is performed. Firstly, a 2(5-2) fractional factorial design for screening the significant variables is used. Secondly, a central composite design for optimizing them is carried out. The best experimental conditions are the followings: poly(di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…Data from Tomlin (2000) Food Anal. Methods (2011) 4:293-299 On the basis of the literature and the experience of the laboratory, different variables were selected to define the experimental field in the SPME procedure (Beltran et al 2000;Zambonin et al 2002;Lasa et al 2006;López et al 2007;Cortés-Aguado et al 2008;Zuazagoitia et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Data from Tomlin (2000) Food Anal. Methods (2011) 4:293-299 On the basis of the literature and the experience of the laboratory, different variables were selected to define the experimental field in the SPME procedure (Beltran et al 2000;Zambonin et al 2002;Lasa et al 2006;López et al 2007;Cortés-Aguado et al 2008;Zuazagoitia et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…ECH, similarly to other volatile organic compounds, has been determined in water by gas chromatography (GC), although this can require multi‐stage and time‐consuming procedures prior to the chromatographic analysis. The methods involved are most often based on isolation and/or enrichment techniques as dynamic headspace purge and trap,6, 7 static headspace,7, 8 liquid‐liquid extraction (LLE),8 solid‐phase extraction (SPE),5, 8 or solid‐phase microextraction (SPME) 8–10. GC determination has been carried out by using detection systems as electron capture detection (ECD),5, 7, 9, 12 flame ionization detection (FID)9, 10, 12 and mass spectrometry (MS) 10–13…”
mentioning
confidence: 99%
“…From the literature review there were few analytical methods which have been reported for Epichlorohydrin such as GC methods [8] …”
Section: Rivaroxaban Is Chemically 5-chloro-n-({(5s)-2-oxo-3-[4-(3-oxmentioning
confidence: 99%